(untitled) (Journal of Environmental Science and Natural Resources, 2012)
An experiment was conducted at the Horticulture Farm, Bangladesh Agricultural University, Mymensingh to evaluate the response of Biomeal, a commercial organic fertilizer in combination with inorganic fertilizers on growth, yield and quality named of carrot. The maximum gross yield (29.27 t ha-1) of carrot was obtained from T4 treatment [recommended dose of inorganic fertilizers (RDIF) + ½ recommended dose of Biomeal (RDB)], while the second lowest gross yield (18.73 t ha-1) was recorded in alone RDB treatment. Carrot plants treated with RDIF showed the highest values for fresh weight of individual root (67.13 g), marketable yield (18.74 t ha-1), shoot length (47.87 cm), individual root diameter (10.91 mm) and nitrogen content in carrot (2.48%). Among the biochemical properties, the maximum amount of reducing sugar and total sugar (5.15 and 10.51%, respectively) were obtained from T7 treatment (RDIF + RDB). In context of carotene, the highest amount (4.92%) was found in T4 treatment (RDIF + ½ RDB). Considering major nutrients and biochemical properties of carrot, it can be inferred that Biomeal alone is not sufficient enough but it has positive influence when it is applied in combination with inorganic fertilizers. The study also revealed that there was no significant contribution of Biomeal to increase organic carbon, N, P, S and Ca content in post harvest soils. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11551 J. Environ. Sci. & Natural Resources, 5(1): 39 - 45, 2012